Living With COVID-19: A Systemic and Multi-Criteria Approach to Enact Evidence-Based Health Policy - Raboisson, Didier; Lhermie, Guillaume (Frontiers in Public Health, 2020)
COVID-19 (Corona virus disease 2019) lockdown lifting requires at short and medium terms a holistic and evidence-based approach of health population management, based on combining risk factors and bio-economic outcomes including actors’ behaviors. This dynamic and global approach of health control is necessary to deal with the new paradigm of living with an infectious disease disrupting our individual freedom and behaviors. The challenge for policymakers consists of defining a lockdown lift method and follow-up (middle term rules) that best meets resumption of economic activity, societal well-being and containment of the outbreak. There is no simple and ready-to-use way for this since it means considering several competing objectives at the same time and continuously adapting the strategy and rules, ideally at local scale. We propose a framework to create a precision evidence-based health policy that simultaneously considers public health, economic and societal dimensions while accounting for constraints and uncertainty. It is based on four following principles: integrating multiple and heterogeneous information, accepting to navigate with uncertainty, adjusting the strategy dynamically with feedback mechanisms, and managing clusters through a multi-scalar conception. The evidence-based policy intervention for COVID-19 obtained includes scientific background via epidemiologic modelling and bioeconomic modelling. A set of quantitative and qualitative indicators are used as feedback to precisely monitor the societal-economic-epidemiological dynamics, allowing tightening or loosening measures before the epidemic damage may (re-)occur. This altogether allows an evidence-based policy that steers the strategy with precision and avoid any political shock.